Photon-pair generation using inverse-designed thin-film lithium niobate mode converters - Kwon, Kiwon; Heo, Hyung Jun; Lee, Dongjin; Kim, Hyeongpin; Jang, Hyeong Soon; Shin, Woncheol; Lim, Hyang Tag; Kim, Yong Su; Han, Sang Wook; Kim, Sangin; Shin, Heedeuk; Kwon, Hyounghan; et al. (Frontiers in Optics, FiO 2024 in Proceedings Frontiers in Optics + Laser Science 2024 (FiO, LS) - Part of Frontiers in Optics + Laser Science 2024, 2024)
Spontaneous parametric down-conversion (SPDC) generates entangled photon pairs.We employ modal phase matching in a straight waveguide with an inverse-designed mode converter.This approach significantly improves SPDC efficiency compared to a waveguide without a converter.
Keywords: Entangled photon pairs; Lithium niobate; Modal phase matching; Mode converter; Photon pairs generations; Spontaneous parametric down-conversion; Straight waveguides; Thin-films